2021
DOI: 10.1186/s12866-021-02141-1
|View full text |Cite
|
Sign up to set email alerts
|

The lung microbiota in Korean patients with non-tuberculous mycobacterial pulmonary disease

Abstract: Background The microbiota of the lower respiratory tract in patients with non-tuberculous mycobacterial pulmonary disease (NTM-PD) has not been fully evaluated. We explored the role of the lung microbiota in NTM-PD by analyzing protected specimen brushing (PSB) and bronchial washing samples from patients with NTM-PD obtained using a flexible bronchoscope. Results Bronchial washing and PSB samples from the NTM-PD group tended to have fewer OTUs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In previous studies, the microbiota diversity in respiratory samples from patients with NTM-PD was significantly lower than that in samples from healthy subjects, which is consistent with our findings [ 6 , 7 , 26 ]. In addition, our study showed that the lung microbiota composition differs between patients with NTM-PD classified according to BMI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In previous studies, the microbiota diversity in respiratory samples from patients with NTM-PD was significantly lower than that in samples from healthy subjects, which is consistent with our findings [ 6 , 7 , 26 ]. In addition, our study showed that the lung microbiota composition differs between patients with NTM-PD classified according to BMI.…”
Section: Discussionsupporting
confidence: 93%
“…However, studies on lower airway microbiota in NTM-PD frequently identified Pseudomonas , Rhadococcus , and Actinomycetales . These bacteria are known to co-infect with NTM-PD [ 26 , 27 ]. Strikingly, the abundance of Haemophilus , Neisseria , and Burkholderiales was higher in patients with NTM-PD with a low BMI than that in patients with NTM-PD with a standard or high BMI, indicating that the BMI can be considered a factor influencing the microbial communities associated with and pathogenesis of NTM infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these studies, in our study, Acinetobacter was more abundant at non-involved sites of lung tissues, suggesting that the abundance of Acinetobacter decreased with invasion of the lung by various other bacteria, including NTM, possibly due to a competitive relationship with other bacteria. Only one South Korean study has reported that Enhydrobacter abundance is decreased in bronchial washing fluid from NTM-PD patients, but they did not find significant clinical implications [16]. Further studies are required to evaluate whether Acinetobacter plays a role in the pathogenesis of NTM-PD, whether it exhibits antagonism against NTM, and how it affects the host's innate immune system.…”
Section: Plos Onementioning
confidence: 99%
“…To explain the heterogeneity of the disease course or pathogenesis of NTM-PD, microbiome studies have been performed using various respiratory samples (e.g., alveolar fluid, oral washings, and sputum), and they have suggested the involvement of several dominant bacterial taxa [13][14][15][16]. However, these studies had some limitations, such as between-study discrepancies, possible sample contamination, insufficient sample sizes, or difficulties in the selection of controls.…”
Section: Introductionmentioning
confidence: 99%
“…In a microbiome study of oral washes, induced sputum, and bronchoalveolar lavage samples, Mycobacterium was identified in 27% of NTM positive samples tested along with other common oral commensals [59] . In a Korean cohort, lower microbial richness was observed among 11 NTM PD patients and 10 controls over the age of 57 years using bronchial washings [60] . Additional information about the lung microbiome of older adults are sure to come in the future and may reveal novel prognostic indicators of lung health status to forecast the likelihood of individuals developing NTM PD.…”
Section: Introductionmentioning
confidence: 91%